The effect of personal and socio economic variables on the knowledge, attitude and belief of farm workers about HIV/AIDS before and after a HIV/AIDS intervention programme - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2013)
Dissertation (MSC (Agricultural Extension))--University of Pretoria, 2007.